A Comparative Clinical Study to Evaluate the Effect of Applying Additional Conservative Procedures on Healing of Periapical Lesions (Journal of Hama University, 2021)
Aim: This research aims to investigate the effect of pharmacologically and mechanical stimulation of the periapical lesion area (which is accomplished through the root canal without any surgical procedures) in the healing of relatively large periapical lesions.Material and Methods: The study included a conservative endodontic treatment of 40 cases with periapical lesion, during two visits, a calcium hydroxide dressing was applied between them. The cases were divided into two equal groups: In the first group, endodontic treatment was performed by the traditional method, and in the second group, the mechanical stimulation process was applied in the visit of canal preparation (active non-surgical drainage) and drug stimulation application in the visit of canal filling (injection of Metapex into the lesion), cases were monitored clinically and radiographically over four different times (3 months, 6 months, 9 months, 12 months).Results: The success rate in the third observation time was 50% in the first group compared to 90% in the second group, with statistically significant differences, and in the fourth time the success rate was 75% in the first group compared to 95% in the second group with statistically significant differences.Conclusions: This clinical experience demonstrated the major role of pharmacologically and mechanical stimulation in the healing of large periapical lesions and increasing the speed of healing for these lesions without the need for surgical procedures